Psychoeducation as A Preventive Effort For Bullying Behavior In Students at MTsN X, Gorontalo City - Renaldi Ointu; Djudiyah Djudiyah (Jurnal Indonesia Sosial Sains, 2026)
Stress is a common condition in daily life. Knowing the exact definition of bullying, influencing factors and efforts to overcome bullying in the school environment properly through psychoeducation is expected to increase students' knowledge about bullying. This research aims to test the effectiveness of psychoeducation in improving MTS students' understanding of bullying prevention. The study used a one-group pretest–posttest design with 20 active students at MTS N X Gorontalo City. Interventions were given in three sessions through presentation and simulation methods combined with video activities on the impact of bullying / Understanding measurement was carried out using questionnaires with open-ended questions. The results of the analysis obtained t = -8.629 with p = 0.00 (p<0.01). This suggests that there is a significant difference in knowledge understanding of bullying before and after psychoeducation. Mean post-test (M = 23.75; SD = 1.44) is greater than the mean pre-test (M = 19.35) and post-test (M = 23.75). This shows that psychoeducation is able to improve students' understanding of bullying.   The very large effect size value (Cohen's d = 2.28) confirms that this intervention has a very strong practical impact. These findings show that psychoeducation is quite effective in helping students understand what bullying is, the forms of bullying, the impact of bullying and how to prevent bullying. This program has the potential to be an alternative to preventive education that is easy to apply in schools